Influence of a Hyperglycemic Microenvironment on a Diabetic Versus Healthy Rat Vascular Endothelium Reveals Distinguishable Mechanistic and Phenotypic Responses - Haspula, Dhanush; Vallejos, Andrew K.; Moore, Timothy M.; Tomar, Namrata; Dash, Ranjan K.; Hoffmann, Brian R. (Frontiers in Physiology, 2019)
Hyperglycemia is a critical factor in the development of endothelial dysfunction in type 2 diabetes (T2D). Whether hyperglycemic states result in a disruption of similar molecular mechanisms in endothelial cells under both diabetic and non-diabetic states, remains largely unknown. This study aimed to address this knowledge gap through molecular and functional characterization of primary cardiac microvascular endothelial cells (RCMVECs) derived from the T2D Goto-Kakizaki (GK) rat model in comparison to control Wistar Kyoto (WKY) in response to a normal (NG) and hyperglycemic (HG) microenvironment. GK and WKY RCMVECs were cultured under NG (4.5 mM) and HG (25 mM) conditions for three weeks, followed by tandem mass spectrometry (MS/MS), qPCR, tube formation assay, microplate based fluorimetry, and mitochondrial respiration analyses. Following database matching and filtering (false discovery rate ≤5%, scan count ≥10), we identified a greater percentage of significantly altered proteins in GK (7.1%, HG vs NG), when compared to WKY (3.5%, HG vs NG) RCMVECs. Further stringent filters (log2ratio of >2 or <-2, p<0.05) followed by enrichment and pathway analyses of the MS/MS and quantitative PCR datasets (84 total genes screened), resulted in the identification of several molecular targets involved in angiogenic, redox and metabolic functions that were distinctively altered in GK as compared to WKY RCMVECs following HG exposure. While the expression of thirteen inflammatory and apoptotic genes were significantly increased in GK RCMVECs under HG conditions (p<0.05), only 2 were significantly elevated in WKY RCMVECs under HG conditions. Several glycolytic enzymes were markedly reduced and pyruvate kinase activity was elevated in GK HG RCMVECs, while in mitochondrial respiratory chain activity was altered. Supporting this, TNFα and phorbol ester (PMA)-induced ROS production were significantly enhanced in GK HG RCMVECs when compared to baseline levels (p<0.05). Additionally, PMA mediated increase was the greatest in GK HG RCMVECs (p<0.05). While HG caused reduction in tube formation assay parameters for WKY RCMVECs, GK RCMVECs exhibited impaired phenotypes under baseline conditions regardless of the glycemic microenvironment. We conclude that hyperglycemic microenvironment caused distinctive changes in the bioenergetics and REDOX pathways in the diabetic endothelium as compared to those observed in a healthy endothelium.